CHILDHOOD OBESITY (Fiep Bulletin - online, 2011)
The increase of individuals with disorders of nutritional education is that the problem of obesity grows more each year. The study was based on elevation of obese levels in recent years in which the physical education teachers used procedures for preventing obesity of students in school. Schools have to promote events for their pupils, in order to clarify the health risks that obesity can bring. With these events, browse stress health prevention, along with the change of style and quality of life. For this survey was conducted a qualitative descriptive study with physical education teachers, through the application of a questionnaire with twelve questions. Note that 47% of students in schools are above weight and that is why it is very large number of pupils excluded in physical education classes. The professionals who are in the labour market, have enough knowledge to be able to work in preventing obesity.
Keywords: Eating disorders; Obesity; Prevention of health